Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan (Studi Pada Divisi F&B Yogya Sunda Heritage 60 Bandung) - Subardjo, Euis Rahma Nursyifa; Zulkarnaen, Wandy; Suwarna, Asep (Universitas Muhammadiyah Metro, 2023)
This research was conducted at the F&B Division Of Yogya Sunda Heritage 60 Bandungwhich is a company engaged in retail, food and beverage production. The purpose of thisstudy was to analyse the effect of the work environment on employee performance todetermine the constraints on employee performance and provide solutions to theseconstraints. The method used in this research is to use verification and descriptive researchwith a quantitative approach, and data collection techniques through questionnaires,literature studies, interviews and observations. This method can help to measure the effect ofa variable by using SPSS data processing. The sample of this research is 32 respondents. Theresults of the analysis show that, based on the t-test, there is a significant positive effectbetween the work environment on the performance of the employees of the F&B Division OfYogya Sunda Heritage 60 Bandung indicating that the t value > t table (14,044 > 1,684).Thus Ho is rejected and Ha is accepted, which means that there is a significant influencebetween the work environment on employee performance. That is, the higher the workenvironment, the higher the performance. To determine the magnitude of the influence of thework environment on performance, it can be seen in the R Square column. The amount of RJurnal Manajemen DiversifikasiVol. 3. No. 3 (2023)494Square (R2) is 868. So it can be concluded that the work environment can contribute 86.8%to employee performance. And the other 13.2% are still influenced by other factors.